2001
DOI: 10.1007/bf02830562
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, characterization, and in vivo evaluation of salmon calcitonin microspheres

Abstract: Purpose. This study was done to prepare, characterize, and evaluate salmon calcitonin (sCT) microspheres (ms) in vivo using a low molecular weight, hydrophilic 50:50 poly (D,L-lactide-coglycolide) polymer (PLGA). Methods. sCT ms were prepared by a dispersion/solvent extraction/evaporation process and characterized for drug content, particle size, surface morphology, and structural integrity of encapsulated peptide. Peptide stability and binding to the polymer was studied in 0.1 M phosphate buffer (PB), pH 7.4,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 16 publications
(13 reference statements)
0
9
0
Order By: Relevance
“…At the end of 2 weeks, addition of free sCT at the 2 concentrations along with blank ms did not decrease the total amount of resorption as much as that with the addition of free sCT at 10 and 250 nM. Previous adsorption studies of sCT to blank ms had shown that as much as 20 µg of sCT was bound to 1 mg of blank ms at pH 7.4 (pH of the culture medium) [ 10]. Therefore, at concentrations of 10 nM (0.03 µg sCT/mL) and 250 nM (0.86 µg sCT/mL) almost all of the sCT should be adsorbed to 1 mg of blank ms (at the end of week 2) leaving none or very little available for binding to cells.…”
Section: Discussionmentioning
confidence: 85%
See 4 more Smart Citations
“…At the end of 2 weeks, addition of free sCT at the 2 concentrations along with blank ms did not decrease the total amount of resorption as much as that with the addition of free sCT at 10 and 250 nM. Previous adsorption studies of sCT to blank ms had shown that as much as 20 µg of sCT was bound to 1 mg of blank ms at pH 7.4 (pH of the culture medium) [ 10]. Therefore, at concentrations of 10 nM (0.03 µg sCT/mL) and 250 nM (0.86 µg sCT/mL) almost all of the sCT should be adsorbed to 1 mg of blank ms (at the end of week 2) leaving none or very little available for binding to cells.…”
Section: Discussionmentioning
confidence: 85%
“…Furthermore, free sCT, either alone or along with blank ms, was added to the cultures only twice a week for 4 weeks. Previous studies at pH 7.4, 37°C had shown that almost 37% of sCT degraded within 24 hours and 100% by 3 days [10]. Consequently, the frequency of addition of free sCT was less than optimal and could have resulted in the lack of dose response.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations